Proceedings of the 30th Annual ACM Symposium on User Interface Software and Technology 2017
DOI: 10.1145/3126594.3126639
|View full text |Cite
|
Sign up to set email alerts
|

CommandBoard

Abstract: Figure 1. CommandBoard creates a new command gesture input space above a soft keyboard. Users can: a) type 'happy' and use a dynamic guide to style it as bold; b) type 'brightn', draw an execute gesture and adjust the brightness slider; c) type 'sans', choose 'sans mono' and draw an execute gesture to change the font; d) type 'color', select yellow in the marking menu to change the brush color.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…(1) We offer a post hoc correction algorithm that infers a user's correction intention in the current entered sentence based on the newly entered word. (2) In our user study, we found both tap typing and gesture typing are appropriate input modalities for JustCorrect. Based on these fndings, we propose two forms of JustCorrect: JustCorrect-Tap and JustCorrect-Gesture.…”
Section: Introductionmentioning
confidence: 80%
“…(1) We offer a post hoc correction algorithm that infers a user's correction intention in the current entered sentence based on the newly entered word. (2) In our user study, we found both tap typing and gesture typing are appropriate input modalities for JustCorrect. Based on these fndings, we propose two forms of JustCorrect: JustCorrect-Tap and JustCorrect-Gesture.…”
Section: Introductionmentioning
confidence: 80%
“…We could push the idea of Keyword Search Bar further by letting users choose if they want to execute the feature right away as proposed by [1,25], or rather learn how to find the feature within the UI (as described in the current Keyword Search Bar concept). This insight points to new dimensions to support expertise transfer across modality, for example between hotkeys and gesture shortcuts.…”
Section: Discussion and Implications For Designmentioning
confidence: 99%
“…For example, P46 failed to edit a MS Word file on her smartphone because she could not find the 'undo' icon: "I needed to fill-in a grid (skills questionnaire) that was fairly short and I could potentially type up everything using a smartphone. There is no 'undo' feature that would correct messed up formatting changes" -this is particularly interesting since the mobile app of MS Word actually includes an 'undo' feature, but users must scroll the icon bar to access it 1 . Similarly, P8 thought that the "Heading" feature was missing from the smartphone version of Google Doc, but during the follow-up interview, she immediately located the feature as she was showing her mobile app.…”
Section: Switching From Pc To Smartphone Versions Was Frustratingmentioning
confidence: 99%
See 1 more Smart Citation
“…CommandBoard [1] takes advantage of the user's ability to recall command names: users simply gesture-type the command, followed by an 'execute' /\ gesture above the keyboard, to invoke it. Gestures that stop within the keyboard area are interpreted as words, whereas gestures that end in the space above are interpreted as commands.…”
Section: Mojiboard Background Rationalementioning
confidence: 99%